Analisis Khat Surat Al-Fātikhah Dalam Mushaf Al-Qur’an Cetakan Menara Kudus Tahun 1974 M - Ahmad Fauzan; Elya Munfarida (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
The Qur'an was revealed by bringing messages, concepts, and rules for humans, so that many Muslim and non-Muslim academic circles study the Qur'an as the object of their study. In this study, the writer chooses a Mushaf Kudus that printed 1974 as the object of this study. This manuscript is one of the famous manuscripts with its corner verse system, besides being easy to remember, writing and decoration are also clear, bright, beautiful, unique and attractive to the public. In terms of the khat’s rules, the writing of this manuscript uses khat naskhī. This khat becomes popular after the experts of khat redesign this khat. Until now, the writing of the Qur'an is synonymous with stylized writing khat naskhī, including the Mushaf Kudus. However, in the use of the khat’s rules, this is not in accordance with the provisions of writing khat naskhī.Therefore, the writer chooses an art of khat to make as an alternative method in analyzing it. The writer hopes that this study will become a new insight and can help scientific discourse to reveal the history and heritage of Islamic art and culture in the Nusantara.